Vulnerability of the North Water ecosystem to climate change - Sofia Ribeiro (Nature Portfolio, 2021)
The North Water polynya is a unique but vulnerable ecosystem, home to Indigenous people and Arctic keystone species. New palaeoecological records from Greenland suggest human abandonment c. 2200–1200 cal yrs BP occurred during climate-forced polynya instability, foreshadowing future ecosystem declines.